Recent Advances in the Application of Essential Oils as Potential Therapeutic Candidates for Candida-Related Infections - Tran, Hoang N. H.; Udoh, Stephanie; Russell, Grace; Okeyoyin, Oluwadamilola R.; Aftab, Sofia; Rodriguez, Isabela; Tabe, Ebot S.; Adukwu, Emmanuel C. (Applied Microbiology (Basel), 2022)
Candidiasis (oral, vulvovaginal, or systemic bloodstream infections) are important human fungal infections associated with a high global prevalence in otherwise healthy adults but are also opportunistic infections in immunocompromised patients. With the recent discovery of the multidrug resistant—and often difficult to treat—Candida auris, as well as the rising costs associated with hospitalisations and the treatment of infections caused by Candida species, there is an urgent need to develop effective therapeutics against these pathogenic yeasts. Essential oils have been documented for many years as treatments for different ailments and are widely known and utilised in alternative and complementary therapies, including treating microbial infections. This review highlights knowledge from research on the effects of medicinal plants, and in particular, essential oils, as potential treatments against different Candida species. Studies have been evaluated that describe the experimental approaches used in investigating the anticandidal effects of essential oils (in vivo and in vitro), the established mode of action of the different compounds against different Candida species, the effect of a combination of essential oils with other compounds as potential therapies, and the evidence from clinical trial studies.